2015
DOI: 10.1186/s13059-015-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling heterogeneous susceptibility and the evolution of breast cancer using a systems biology approach

Abstract: BackgroundAn essential question in cancer is why individuals with the same disease have different clinical outcomes. Progress toward a more personalized medicine in cancer patients requires taking into account the underlying heterogeneity at different molecular levels.ResultsHere, we present a model in which there are complex interactions at different cellular and systemic levels that account for the heterogeneity of susceptibility to and evolution of ERBB2-positive breast cancers. Our model is based on our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 50 publications
1
71
0
Order By: Relevance
“…Establishing the temporal relationships between mutations has been accomplished in some tumor types by utilizing multiregion sequencing. These studies have yielded compelling phylogenetic trees showing branched evolution of the tumor cell populations . However, these studies use a limited number of specimens making the findings difficult to generalize, especially to other tumor types.…”
mentioning
confidence: 99%
“…Establishing the temporal relationships between mutations has been accomplished in some tumor types by utilizing multiregion sequencing. These studies have yielded compelling phylogenetic trees showing branched evolution of the tumor cell populations . However, these studies use a limited number of specimens making the findings difficult to generalize, especially to other tumor types.…”
mentioning
confidence: 99%
“…We identified QTLs associated with the heterogeneous behavior of the different pathophenotypes of the disease, and QTLs associated with the variability of the different intermediate phenotypes studied. After carrying out this study, we observed that most of the tumor QTLs associated with different pathophenotypes did not overlap with the QTLs associated with intermediate phenotypes, even with those that could be expected to be strongly associated with tumor variability, such as those related with tumor cell signaling . Thus, an intermediate phenotype associated with the pathogenesis of a complex trait, in turn presents its own variability along the population, and is also controlled by a number of QTLs that seem to be different.…”
Section: Missing Heritability Of Complex Traits Could Be Partly Explamentioning
confidence: 93%
“…such as those related with tumor cell signaling [76]. Thus, an intermediate phenotype associated with the pathogenesis of a complex trait, in turn presents its own variability along the population, and is also controlled by a number of QTLs that seem to be different.…”
Section: Pr Ospects and Overviewsmentioning
confidence: 99%
“…1A in Data in Brief [20]), and the mice developed a luminal-type breast tumour within a median of 7 months in the FVB genetic background [21]. The transgene-positive F1 mice were mated with FVB non-transgenic mice to generate the first generation of backcross mice [22]. Regarding the resultant genetic backgrounds, since the 147 mice were generated by a backcross, each had a variable mixture of the genetic backgrounds of B6 and FVB.…”
Section: Micementioning
confidence: 99%
“…Some of the specific signalling molecules from pathways related to metabolism were measured in liver tissue [22] (see material and methods in Data in Brief [20]).…”
Section: Quantification Of the Liver Signalling Pathways Associated Wmentioning
confidence: 99%